Family Caregiving in Serious Illness in the United States: Recommendations to Support an Invisible Workforce. (10th May 2019) - Bell, Janice F.; Whitney, Robin L.; Young, Heather M.
Abstract : Family caregivers provide the vast majority of care for individuals with serious illness living in the community but are not often viewed as full members of the healthcare team. Family caregivers are increasingly expected to acquire a sophisticated understanding of the care recipient's condition and new skills to execute complex medical or nursing tasks, often without adequate preparation and support, and with little choice in taking on the role. This review draws on peer‐reviewed literature, government reports, and other publications to summarize the challenges faced by family caregivers of older adults in the context of serious illness and to identify opportunities to better integrate them into the healthcare workforce. We discuss promising approaches such as inclusion of family caregivers in consensus‐based practice guidelines; the "no wrong door" function, directing consumers to needed resources, regardless of where initial contact is made; and caregiver‐friendly workplace policies allowing flexible arrangements. We present specific recommendations focusing on research, clinical practice, and policy changes that promote family‐centered care and improve outcomes for caregivers as well as persons with serious illness. J Am Geriatr Soc 67:S451–S456, 2019.